2000
DOI: 10.1034/j.1600-0420.2000.078s230042.x
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy Comparison of Emedastine 0.05% Ophthalmic Solution Compared to Levocabastine 0.05% Ophthalmic Suspension in Pediatric Subjects with Allergic Conjunctivitis

Abstract: ABSTRACT.Purpose: To determine the efficacy and tolerance of emedastine 0.05% ophthalmic solution compared to levocabastine 0.05% ophthalmic suspension in pediatric subjects. Methods and Materials: In a randomized, double-masked, parallel controlled study, emedastine 0.05% ophthalmic solution BID was compared to levocabastine 0.05% ophthalmic suspension BID, for control of the signs and symptoms of allergic conjunctivitis in pediatric subjects ages 3-16. Subjects who met all inclusion and exclusion criteria re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Emedastine 0.05% appears to be more potent and selective than levocabastine [27, 28]. Indeed, in direct comparison with levocabastine, emedastine proved significantly more effective in alleviating signs of seasonal allergic conjunctivitis [27, 28].…”
Section: Management Of Vkcmentioning
confidence: 99%
See 1 more Smart Citation
“…Emedastine 0.05% appears to be more potent and selective than levocabastine [27, 28]. Indeed, in direct comparison with levocabastine, emedastine proved significantly more effective in alleviating signs of seasonal allergic conjunctivitis [27, 28].…”
Section: Management Of Vkcmentioning
confidence: 99%
“…Indeed, in direct comparison with levocabastine, emedastine proved significantly more effective in alleviating signs of seasonal allergic conjunctivitis [27, 28]. No specific studies in VKC have been performed.…”
Section: Management Of Vkcmentioning
confidence: 99%
“…Studies in patients with AC showed that it provided significantly more relief of itching and hyperemia than placebo at a duration of at least 4 hours [26]. Emedastine also had the advantage of being approved for use in patients 3 years of age or older [27]. With these findings, the evolution of the dual-acting molecules had begun.…”
Section: Second-generation Ocular Antihistaminesmentioning
confidence: 96%
“…However, topical immune suppressive agents, such as corticosteroids and ciclosporin, are used for more severe types, such as VKC. Many randomized, double-blinded, controlled clinical trials have demonstrated the efficacy of antihistamines in providing relief of many symptoms of allergic conjunctivitis (e.g., itching, redness, tearing, chemosis) [62][63][64][65][66][67][68][69][70][71][72]. One recent prospective, randomized, double-blinded, and placebo-controlled trial (n = 100) showed that 0.05% emedastine difumarate ophthalmic solution (twice per day) was significantly more effective than placebo, and similar to other ophthalmic solutions (olopatadine hydrochloride, ketotifen fumarate, epinastine hydrochloride) [62].…”
Section: Allergic Conjunctivitismentioning
confidence: 99%